Comparative mitogenomics of freshwater snails of the genus Bulinus, obligatory vectors of Schistosoma haematobium, causative agent of human urogenital schistosomiasis - Si-Ming Zhang; Lijing Bu; Lijun Lu; Caitlin Babbitt; Coen M. Adema; Eric S. Loker (Scientific Reports)
Abstract Among the snail genera most responsible for vectoring human-infecting schistosomes, Bulinus, Biomphalaria, and Oncomelania, the former is in many respects the most important. Bulinid snails host the most common human blood fluke, Schistosoma haematobium, responsible for approximately two-thirds of the estimated 237 million cases of schistosomiasis. They also support transmission of schistosomes to millions of domestic and wild animals. Nonetheless, our basic knowledge of the 37 Bulinus species remains incomplete, especially with respect to genome information, even including mitogenome sequences. We determined complete mitogenome sequences for Bulinus truncatus, B. nasutus, and B. ugandae, and three representatives of B. globosus from eastern, central, and western Kenya. A difference of the location of tRNA-Asp was found between mitogenomes from the three species of the Bulinus africanus group and B. truncatus. Phylogenetic analysis using partial cox1 sequences suggests that B. globosus is a complex comprised of multiple species. We also highlight the status of B. ugandae as a distinct species with unusual interactions with the S. haematobium group parasites deserving of additional investigation. We provide sequence data for potential development of genetic markers for specific or intraspecific Bulinus studies, help elucidate the relationships among Bulinus species, and suggest ways in which mitogenomes may help understand the complex interactions between Schistosoma and Bulinus snails and their relatives.